Low-threshold germanium laser for chip-scale LiDAR - Nam, Donguk (2020)
In this paper, we present our recent result on germanium lasers on silicon that operate at a low threshold. We will introduce our innovative strain engineering platforms that can create direct bandgap germanium nanowires by inducing >5% elastic tensile strain. Then, we will present our first experimental observation of low-threshold optically pumped lasing in strained germanium nanowires. We will also discuss the possibility of our on-chip lasers for the ultimate realization of chip-scale LiDAR systems.